The political uses of the past in Nordic media discourses: An integrative systematic literature review - Menke Manuel (Nordicom Review)
In this article, an integrative systematic literature review of 47 journal articles is conducted to gain knowledge about the political uses of the past in Nordic media discourses. The sample includes literature about diverse memory agents and institutions in varying media contexts, such as online communication, journalism, film, television, and documentaries, to gain a broader understanding of actors and themes in mediated public negotiations of the past in the Nordics. The analysis reveals that political uses of the past vary in the studied areas of far-right online discourses, media representations of minority pasts, mediated commemoration of war and terrorism, as well as archives. The review aims to integrate these research strands to initiate knowledge exchange by synthesising insights from the different perspectives and academic provinces engaging in research on media, politics, and the past.